Teachers’ Responses to Bullying Questionnaire: A Validation Study in Two Educational Contexts - van Gils, Fleur Elisabeth; Colpin, Hilde; Verschueren, Karine; Demol, Karlien; ten Bokkel, Isabel Maria; Menesini, Ersilia; Palladino, Benedetta Emanuela (Frontiers in Psychology, 2022)
Given the high prevalence and dramatic impact of being bullied at school, it is crucial to get more insight into how teachers can reduce bullying. So far, few instruments have measured elementary teachers’ responses to bullying. This study investigated the validity of the student-reported Teachers’ Responses to Bullying Questionnaire. The factor structure and measurement invariance were tested across two educational contexts among fourth and fifth grade students from Italy (n = 235) and Belgium (n = 667). Furthermore, associations between student-perceived teachers’ responses and students’ bullying behavior were examined. Confirmatory Factor Analysis supported the predicted five-factor structure, distinguishing Non-Intervention, Disciplinary Methods, Group Discussion, Mediation, and Victim Support. A partial factor means invariance model was found, allowing for valid comparisons between the Italian and Belgian educational contexts. Significant associations were found between self-reported, but not peer-nominated, bullying behavior and most student-perceived teachers’ responses.